Formulation Of 3D Euclidean Distance For Network Clustering In Wireless Sensor Network - Kalid Abdlkader Marsal; Azni Hazlizan Ab Halim; Farida Hazwani Mohd Ridzuan (COMPUSOFT, 2024)
Volume :8 Issue :9